PENGARUH BAHAN ANTIKARIES BEBERAPA TANAMAN HERBAL YANG DIKOMBINASI DENGAN PASTA GIGI YANG MENGANDUNG FLUORIDE TERHADAP PERTUMBUHAN STREPTOCOCCUS MUTANS SECARA IN VITRO: ANTICARIES EFFECT OF SOME HERBAL PLANTS COMBINED WITH FLUORIDE TOOTH PASTE ON THE GROWTH OF STREPTOCOCCUS MUTANS (Dentika: Dental Journal, 2010)
Dental caries is the most commonly oral disease and the main bacterial cause of it is Streptococcus mutans (S. mutans). Fluoride, xylitol, betel leaf and siwak are the substances often found in toothpaste. The effect of them inhibits the growth of S. mutans. The purpose of this study was to determine the effect of herbal plants such as xylitol, betel leaf and siwak that combined with fluoride in toothpaste on the growth of S. mutans (in vitro). S. mutans laboratory strain was exposed to three toothpastes that contained combination of fluoride and each of herbal plants such as xylitol, siwak, and betel leaf. This study also used non herbal toothpaste as a control. The results of ANOVA test on S. mutans colonies growth in media TYS20B showed that there was significant difference (p